ìИМПЕРСКОЕî НАПРАВЛЕНИЕ ПОСТСОВЕТСКОЙ ИСТОРИОГРАФИИ ВТОРОЙ МИРОВОЙ ВОЙНЫ: ПРИЧИНЫ ВОЗНИКНОВЕНИЯ И МЕТОДОЛОГИЯ (Zaporizhzhia Historical Review, 2021)
In clause the reasons of occurrence ìimpareî of a direction a postsoviet historiography of the Second World War are considered; the main form and type of presentation of historical research of the authors of the given direction is placed; the methods of the researches used in the given direction, methodology of their application are detected main and new; the feature of the circuit - requirement to the argument and methodological requirements to it is considered.